Modelling heat and electricity supply in multifamily buildings with energy storage and solar PVs - Borg, Filippa (My University, 2015)
The purpose of this thesis is to investigate how buildings with solar PVs and heat and electricity storage can be operated. The building considered has both a district heating connection and heat pumps, and can buy district heating and electricity on spot price. A model has been created to optimise the energy supply in the building by minimising the running cost utilising the energy storage, the price fluctuations and the produced solar electricity. The conclusion is that the combination of electrical and thermal storage works well, both are useful and contributes to the cost reduction. The running cost can be reduced with 24% with a thermal storage capacity of 1 000 kWhth and an electrical storage of 300 kWhel. The storage capacities reduces the dependencies from the electricity grid and the district heating network. With an electrical storage of 300 kWhel, the building can be self-sufficient on electricity 57% of the hours of the year, while without any storage only 29 %. The decrease in running cost is largest when increasing the electrical storage, since a larger share of the produced PV electricity can be utilised in the building which saves not only the spot price of electricity, but also taxes and grid fees. Due to the large fluctuations in the marginal district heating cost, the share of heat supplied by district heating increases with increased thermal storage. The heat pumps and the district heating can efficiently collaborate. A combination of the two technologies, together with spot price on both electricity and district heating, reduces the running cost of the building regardless of storage size. Utilising energy storage in buildings, as in this thesis, will increase flexibility in the energy system in the building and reduce dependency on the surrounding energy grids.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering